Caracterización de áreas de producción agrícola utilizando sig en la parroquia La Victoria del canton Santa Rosa - Molina Gómez, Julio César (2006)
The systems of geographical information SIG., they are tools every time but used in the processes of economic, territorial and environmental planning, the construction of a geographical database is one of the stages of the classification and of the planning of the agriculture in a canton, at the present time the banana tree cultivations and cocoa generate at one time certain a deficit or an on production in the commercialization in the external or interior markets, leaving this way lost in the agricultural sector; in the parish The Victoria belonging to the canton Santa Rosa and with the technical advice of the Integrated Center of Environmental Geomatica (CINFA), of the University of Loja, he/she was carried out the characterization of the areas of agricultural production using system of geographical information. The objectives were the following ones: 1. gathering, validation and digitalización of the biophysical information of the canton Santa Rosa, 2. Structuring of a geographical base that you/they contain the characteristics of the production area, 3. to Analyze the production volume and commercialization of some sectors of the canton Santa Rosa, the methodology for the first objective, was carried out a gathering of secondary data obtained in the Municipality of the canton Santa Rosa, Provincial Council and the information of the infoplan in different cartographic aspects as: map of vegetable covering, map of curved of level, map of current use, map of net hídrica, texture map, map of towns, geology map, morphology map, map of slopes, maps of roads that were used to elaborate maps in a digital way with biophysical aspects of different sectors of the parish The Victoria. The use of the software like: The Microsoft Excel, Easy traces, CartaLinx and ArcView 3.2 of Esri, they allowed to carry out the digital map of some sectors of the parish The Victoria that you/they are good for new projects. The use of the GPS and the field journey by means of surveys to the producers an information was obtained with each proprietor's different agronomic aspects, giving a banana tree association and cocoa as a result in those sectors, the Systems of Geographical Information (SIG) they have to be used in all the investigation projects, due to the great quantity of information that you can store in these software.